Diagnostic yield of ultrasound guided fine needle aspirations of thyroid nodules at Charlotte Maxeke Johannesburg and Chris Hani Baragwanath academic hospitals - Ncube, Elton (My University, 2019)
INTRODUCTION: Fine needle aspiration of thyroid nodules is a frequently requested and performed procedure in the Department of Radiology at Charlotte Maxeke Johannesburg Academic and Chris Hani Baragwanath Academic Hospitals. The procedure has to be performed and reported according to acceptable guidelines and the diagnostic yield periodically assessed. AIM: To evaluate the diagnostic yield of FNA of thyroid nodules performed at Charlotte Maxeke Johannesburg and Chris Hani Baragwanath Academic Hospitals and to assess for possible pre-analytic variables that affect the quality of cytological specimens obtained. METHOD: A retrospective analysis of ultrasound and FNA of thyroid nodule reports and cytology reports was done. The reports were accessed from the Picture Archiving and Communications System and LabTrack (National Health and Laboratory Service) systems respectively. The reports were assessed for completeness and content, results were entered onto a spread sheet. The diagnostic yield was calculated and correlated with factors known to affect it. RESULTS: A total of 181 nodules were assessed giving a diagnostic yield of 71.8%. The presence of a cytologist was associated with a higher diagnostic yield with a Fischer’s exact p-value of 0.04. Additionally, mixed nodule consistency was associated with a lower non-diagnostic rate. CONCLUSIONS: A significant proportion of the FNAs performed were non-diagnostic with just above a quarter of the samples obtained being evaluated as inadequate. Most of the non-diagnostic samples were reported as containing inadequate cells and/or bloody. There were no pre-analytic extrinsic/technical variables identified as a possible cause.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology. Johannesburg, 2019